Press Law Research Mapping; Using Bibliometrics - Mexsasai Indra,; Ismandianto,; Muchid Albintani,; Belli Nasution, (Technium Social Sciences Journal, 2024)
This research aims to determine the direction of press law research trends, identify relationships between other scientific concepts based on press law keywords. The method used in this research is bibliometric analysis, the data used was taken from Scopus in the period 2013-2023. Data collection was carried out based on the Scopus database. Data collection was carried out using Publish or Perish software as metadata with a total of 26 articles obtained. Data analysis was carried out using Vosviewer software as a bibliometric analysis medium. The results of the research show that press law research mapping has increased, in terms of quantity it has increased. The highest publication growth occurred in 2021, reaching 28 journals (23%), while in 2005 the lowest publication was 2 publications (2%), in 2013 there were no Scopus publications.